IMPACT OF HOMOGENIZATION OF VILLAGE GOVERNANCE FORM IN INDONESIA RELATED TO SOCIAL CHANGES - Deliana, Vita (Jurnal Hukum Peratun, 2022)
Legal changes through modifications or changes in values that exist in society through laws can cause social changes. In this paper, the social change in question is regarding society and government of villages in Indonesia, from the pre-independence era until the post-reformation era. The writing method used in this research is a normative juridical approach using a statutory approach and a conceptual approach. This paper uses the legal-normative method, namely an approach based on legal materials by examining concepts, theories, legal principles, and legislation, as well as literature related to writing. In this paper it is found that changes have occurred since the end of the old order era which uniformed or homogenized the structure of local village government. As a result, many traditional villages are independent without being included in the government structure according to the law, and the community is also becoming more ethnocentric because it is considered that the development carried out is based on the Javanization stereotype.